PENINGKATAN MOTIVASI BELAJAR DAN PEMBEKALAN KEMAMPUAN BERORGANISASI BAGI GENERASI ALPHA SISWA SISWI SMPN 8 JAKARTA PUSAT - Rahayuningsih, Deasy Ariyanti; Ruswidiono, R. Wasisto; Arilyn, Erika Jimena; Beny, Beny (Bajang Institute, 2025)
The community service activity aimed to increase the motivation learning of SMPN 8 students and equipe them with organizational skills. This training was held on October 29, 2024 with a duration 3 hours started from 09.00 until 12.30 in the hall of SMPN 8 Central Jakarta. This activity was attended around 150 students in 7 th grade. The training started from interactive discussion from each speakers with the theme discussion about understanding oneself as an alpha generation, the importance of motivating oneself in learning, developing one's abilities in organizing and becoming a future leader. The interactive discussion was also interspersed with a question, answer session and a game session.The training was ended with the distribution of door prizes and a group photo. This community service activity is expected to equip the alpha generation, namely SMPN 8 Jakarta students, to understand that their lives today coexist and depend on the existence of digital technology whose development is more rapid and instant. The students as the future leader must be able to adapt to current conditions through developing themselves and growing motivation in learning and organizing. Thus, they are expected to have good leadership skills that become role figures or leaders who are honest, trustworthy, reliable, responsible for the environment and have sensitivity (empathy) towards their surroundings amidst the current flow of uncertain information. Kegiatan pengabdian masyarakat ini bertujuan meningkatkan motivasi belajar siswa siswi SMPN 8 serta pembekalan kemampuan mereka dalam berorganisasi. Pelatihan ini diadakan tanggal 29 Oktober 2024 dan berlangsung selama 3 jam yakni pukul 09.00 hingga pukul 12.30 di Aula SMPN 8 Jakarta Pusat. Pelatihan ini dihadiri oleh sekitar 150 siswa siswi kelas 7. Kegiatan pelatihan ini diawali dengan sesi diskusi interaktif dari masing-masing narasumber yang membahas tentang pemahaman diri sebagai generasi alpha, pentingnya memotivasi diri dalam belajar, mengembangkan kemampuan berorganisasi serta menjadi pemimpin di masa mendatang. Sesi diskusi interaktif ini diselingi tanya jawab dan sesi permainan (games). Kegiatan diakhiri dengan pembagian doorprize serta foto bersama. Pelatihan ini diharapkan memberikan pemahaman terhadap generasi alpha yakni siswa siswi SMPN 8 Jakarta bahwa kehidupan mereka saat ini berdampingan dengan perkembangan tehnologi digital yang bergerak cepat dan instan. Mereka selaku generasi penerus dimasa datang hendaknya mampu berdaptasi dengan kondisi terkini melalui upaya mengembangkan diri, meningkatkan motivasi belajar serta kemampuan berorganisasi. Siswa siswi SMPN 8 diharapkan memliki kemampuan leadership yang baik dengan menjadi role figure atau sosok pemimpin yang jujur, amanah serta dapat dipercaya, bertanggungjawab serta memiliki kepekaan (empati) terhadap lingkungan sekitarnya meski saat ini mereka berada ditengah arus ketidakpastian informasi.